2018
DOI: 10.1016/j.neuron.2018.03.048
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging Impaired Response Inhibition and Salience Attribution in Human Drug Addiction: A Systematic Review

Abstract: The impaired response inhibition and salience attribution (iRISA) model proposes that impaired response inhibition and salience attribution underlie drug seeking and taking. To update this model, we systematically reviewed 105 task-related neuroimaging studies (n > 15/group) published since 2010. Results demonstrate specific impairments within six large-scale brain networks (reward, habit, salience, executive, memory, and self-directed networks) during drug cue exposure, decision making, inhibitory control, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

46
404
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 412 publications
(453 citation statements)
references
References 145 publications
(238 reference statements)
46
404
1
2
Order By: Relevance
“…This could reflect the fact that the social alcohol cue‐reactivity and the stimulus‐response compatibility tasks engage partly different (brain) mechanisms. More specifically, whereas cue‐reactivity (e.g., based on the incentive sensitization model of addiction (Robinson & Berridge, , , )) engages the salience and reward brain networks (Zilverstand, Huang, Alia‐Klein, & Goldstein, ), approach tendencies (e.g., seen as an automatic response in the dual‐process models of addiction (Wiers et al., ; Stacy & Wiers, )) require a response and therefore also involve the executive network (Zilverstand et al., ). This difference between the two measures might explain why they are not correlated in the present data and further suggest that cue‐reactivity and approach biases may be independent mechanisms associated with drinking behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…This could reflect the fact that the social alcohol cue‐reactivity and the stimulus‐response compatibility tasks engage partly different (brain) mechanisms. More specifically, whereas cue‐reactivity (e.g., based on the incentive sensitization model of addiction (Robinson & Berridge, , , )) engages the salience and reward brain networks (Zilverstand, Huang, Alia‐Klein, & Goldstein, ), approach tendencies (e.g., seen as an automatic response in the dual‐process models of addiction (Wiers et al., ; Stacy & Wiers, )) require a response and therefore also involve the executive network (Zilverstand et al., ). This difference between the two measures might explain why they are not correlated in the present data and further suggest that cue‐reactivity and approach biases may be independent mechanisms associated with drinking behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Findings supported predictions that brain regions and networks involved are more strongly engaged by drug-related processing and blunted by non-drug-related processing. Data further supported that brain regions implicated in habit (dorsal caudate and putamen) are associated with drug use initiation and relapse, consistent with their role in the transition from voluntary use to compulsive drug-taking behavior [25]. …”
Section: Introductionmentioning
confidence: 65%
“…The complexity of drug addiction at the whole-brain level was recently exemplified in a systematic review of neuroimaging studies of drugs of abuse including nicotine [25]. The review identified consistent impairments in brain function across a range of tasks including cue-exposure, decision making, inhibitory control, and social-emotional tasks, in six functional brain ‘networks’ including regions involved in reward and habit; the canonical salience network (SN), implicated in (re)orienting attention to salient stimuli; executive control network (ECN), implicated in selection of behavioral responses; and default mode network (DMN), implicated in self-referential processing; and regions involved in memory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, the study of individual differences, including sex differences, is also of paramount importance. In general, there is marked underrepresentation of females in neuroimaging studies (or in clinical trials) of drug addiction (Zilverstand et al, 2018). That said, the opposite trend also needs to be taken into account, since males are not well represented in the binge eating disorder literature (Naish et al, 2018).…”
Section: Human Studiesmentioning
confidence: 99%